Assessment of ibuprofen as a neuroprotective agent in chronic cerebral hypoperfusion-induced neurodegeneration in rats. - Saxena, Anil Kumar; Mohd Noor, Mohd Fadly; A.Talib, Norlelawati; Gurtu, Sunil (2012)
Aging related reduction in cerebral blood flow (CBF) has been linked with neurodegenerative disorders including Alzheimer's diseases and dementia. Experimentally, a condition of chronic cerebral hypoperfusion due to reduced can be induced by permanent bilateral occlusion of common carotid arteries (2-vessel occlusion, 2VO) in rats. Since neuroinflammation, leading to neuronal apoptosis and death, is one of the mechanisms which is thought to play a significant role in chronic degenerative neurological disorders, the present study was planned to assess the neuroprotective role of ibuprofen in chronic cerebral hypoperfusion-induced neurodegeneration. Fifteen rats were equally divided into 3 groups. Group A - sham control, Group B - 2VO, and Group C - 2VO-I (treated daily with 50mg/kg orally ibuprofen following 2VO). After 8 weeks, all the rats were euthanized and the hippocampi were isolated. Viable neuronal cell count in the hippocampal CA1 region, hippocampal COX-2 mRNA expression and prostaglandin E2 (PGE-2) levels were estimated. There was a significant difference in neuronal cell death, increasing in COX-2 mRNA expression and PGE-2 levels in 2VO group compared to Sham control group. In ibuprofen treated 2VO rats the viable neuronal cell count of the hippocampal CA-1 region was significantly higher compared to the untreated 2VO group. For the hippocampal COX-2 mRNA expression, the value in the ibuprofen treated 2VO group showed no significant difference when compared to the untreated 2VO group. However, hippocampal PGE-2 levels were found to be significantly lower in ibuprofen treated 2VO rats compared to untreated 2Vo rats. Results indicate that ibuprofen is an effective neuroprotective agent in chronic cerebral hypoperfusion-induced neurodegeneration.